Preservation of bioactive compounds of a green vegetable smoothie using short time-high temperature mild thermal treatment - Castillejo, Noelia; Benito Martinez-Hernandez, Gines; Monaco, Kamila [UNESP]; Gomez, Perla A.; Aguayo, Encarna; Artes, Francisco; Artes-Hernandez, Francisco (Sage Publications Ltd, 2017)
Smoothies represent an excellent and convenient alternative to promote the daily consumption of fruit and vegetables in order to obtain their health-promoting benefits. Accordingly, a green fresh vegetables smoothie (77.2% cucumber, 12% broccoli and 6% spinach) rich in health-promoting compounds was developed. Soluble solids content, pH and titratable acidity of the smoothie were 4.3 +/- 0.4 degrees Bx, 4.49 +/- 0.01 and 0.22 +/- 0.02mg citric acid 100(-1) g fw, respectively. Two thermal treatments to reduce microbial loads and preserve quality were assayed: T1 (3min at 80?) and T2 (45s at 90?). Fresh blended unheated samples were used as control (CTRL). The smoothie presented a viscoelastic behaviour. T1 and T2 treatments reduced initial microbial loads by 1.3-2.4 and 1.4-3.1 log units, respectively. Samples were stored in darkness at 5 and 15?. Colour and physicochemical changes were reduced in thermal-treated samples throughout storage, which were better preserved at 5? rather than at 15?. Vitamin C changes during storage were fitted with a Weibullian distribution. Total vitamin C losses of T1 and T2 samples during storage at 15? were greatly reduced when they were stored at 5?. Initial total phenolic content (151.1 +/- 4.04mg kg(-1) fw) was 44 and 36% increased after T1 and T2 treatments, respectively. The 3-p-coumaroyl quinic and chlorogenic acids accounted the 84.7 and 7.1% relative abundance, respectively. Total antioxidant capacity (234.2 +/- 20.3mg Trolox equivalent kg(-1) fw) remained constant after the thermal treatments and was better maintained during storage in thermal-treated samples. Glucobrassicin accounted the 81% of the initial total glucosinolates content (117.8 +/- 22.2mg kg(-1) fw) of the smoothie. No glucosinolates losses were observed after T2 treatment being better preserved in thermal-treated samples. Conclusively, a short time-high temperature mild thermal treatment (T2) showed better quality and bioactive compounds retention in a green fresh vegetable smoothie during low temperature storage.
Keywords: Phenolic compounds; glucosinolates; vitamin C; antioxidants; quality; beverages